The Mongol empire’s expansion and rethinking research trends in Chinese historical climatology - Ka wai Fan (Humanities & Social Sciences Communications)
Abstract Historical climatology, an emerging interdisciplinary field, seeks to reconstruct reliable climate data to understand the impact of climate change on historical events. This article introduces the underlying reasons for the westward expansion of the Mongol Empire, challenging entrenched assumptions through the lens of climate. It reviews scholarly discourse, focusing in particular on a theory linking Mongol expansion to a global dry period, while juxtaposing this with recent research spearheaded by climatologists. Their findings reveal that Mongol expansion coincided with favorable climatic conditions, casting doubt on the traditional narrative. Additionally, this article probes the use of the Granger Causality Test in Chinese historical climatology, as exemplified by the work of David Zhang. While Zhang’s research underscores correlations between climate fluctuations and historical events, this review initiates conversations regarding the limitations of the test and the necessity of meticulous contextualization. The article concludes by emphasizing the importance of verifying historical facts and considering nuanced historical contexts when employing statistical methods such as the Granger Causality Test in historical climatology. Through critical analysis of the history of the Mongol Empire, this study contributes to a deeper understanding of the complex relationships between climate change and human history, advocating for prudence in drawing causal inferences.